7th International Symposium on Plasma- And Process-Induced Damage
DOI: 10.1109/ppid.2002.1042620
|View full text |Cite
|
Sign up to set email alerts
|

Influence of photoresist pattern on charging damage during high current ion implantation

Abstract: The influence of photoresist pattern on charging damage of gate oxides during high current arsenic implantation is studied. Metal-oxide- semiconductor (MOS) capacitors of 10 mu m/sup 2/ active area and 4.5 nm oxide thickness connected with various types of poly antennas and resist patterns on top were processed, whereby the resist overlapped and/or enclosed the gate electrode during ion implantation. The evaluation of the devices was performed by leakage current and charge to breakdown (Qbd) measurements. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…A yield criterion of 10 -9 A was established to distinguish between damaged and undamaged devices. Additional measurements showed good agreement between leakage current and charge-to-breakdown data [6]. …”
Section: Test Structures and Electricalmentioning
confidence: 61%
See 3 more Smart Citations
“…A yield criterion of 10 -9 A was established to distinguish between damaged and undamaged devices. Additional measurements showed good agreement between leakage current and charge-to-breakdown data [6]. …”
Section: Test Structures and Electricalmentioning
confidence: 61%
“…To study the influence of ion implantation parameters, the wafers were divided into seven groups with three wafers each and implanted as shown in Table II. Former experiments showed that plasma electron flood (PEF) prevents charging damage effectively [6]. Therefore, the electron flood system was turned off to accomplish high damage effects.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations